Legality of the Constitutional Court as a Party and at the Same Time as a Judge in Disputes over the Authority of State Institutions - Sumali; Echaib Samira (Universitas Muhammadiyah Malang, 2022)
Abstract The purpose of this study is to determine the legality of the constitutional court as a party and at the same time as an adjudicator in disputes over the authority of state institutions. The research method used is the normative legal research method. The results showed that the 1945 Constitution never allocated the authority to test executive legal products in the form of Perppu to the Constitutional Court but to the DPR which is commonly known as legislative review. However, the Constitutional Court through decision No. 138/PUU-VII/2009 has added its authority, namely adding Perppu as the object of the litical test of the judicial review law. The consequence of the addition of the authority to test the Perppu is of course likely to cause a conflict of authority between the Constitutional Court versus the DPR. The problem is that the authority to torture and adjudicate legal conflicts between state institutions according to the 1945 Constitution must be carried out through the courts of the Constitutional Court. Therefore, the juridical problem that arises is whether there is legality or constitutionality of the Constitutional Court to try cases concerning its own interests, while on the other hand there is a doctrine of nemo judex idoneus in propria causa which means that judges are not fit to try themselves because of a conflict of interest or conflict of interest. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui legalitas mahkamah konstitusi sebagai salah satu pihak dan sekaligus sebagai ajudikator dalam sengketa kewenangan lembaga negara. Metode penelitian yang digunakan adalah metode penelitian hukum normatif. Hasil penelitian menunjukkan bahwa UUD1945 tidak pernah mengalokasikan kewenangan untuk menguji produk-produk hukum eksekutif dalam bentuk Perppu kepada Mahkamah Konstitusi melainkan kepada DPR yang biasa dikenal dengan judicial review legislatif. Namun, Mahkamah Konstitusi melalui putusan No. 138/PUU-VII/2009 telah menambah kewenangannya, yaitu penambahan Perppu sebagai objek uji litical test uu judicial review. Konsekuensi dari penambahan kewenangan untuk menguji Perppu tentu saja kemungkinan akan menimbulkan konflik kewenangan antara Mahkamah Konstitusi versus DPR. Masalahnya, kewenangan penyiksaan dan mengadili konflik hukum antar lembaga negara menurut UUD 1945 harus dilakukan melalui pengadilan Mahkamah Konstitusi. Oleh karena itu, permasalahan yuridis yang muncul adalah apakah ada legalitas atau konstitusionalitas Mahkamah Konstitusi untuk mengadili perkara-perkara yang menyangkut kepentingannya sendiri, sedangkan di sisi lain terdapat doktrin nemo judex idoneus dalam propria causa yang artinya hakim tidak layak untuk mengadili diri sendiri karena adanya benturan kepentingan atau benturan kepentingan.